PP88 Exploitation of Pineapple Peel Residues, India and Oro Miel Varieties: Extraction of Essential Oils by Hydrodistillation and NADES. Chemical Characterization and Evaluation of Antioxidant Activity - Cupitre Mojica, Monica Gisella; Valencia Sotto, Mayrin Oslany; Paladines Beltrán, Gloria; Galeano García, Paula Liliana (Revista Productos Naturales, 2026)
In Colombia, approximately 32,700 ha of pineapple are cultivated, generating large amounts of peel waste (1). These peels pose an environmental issue but contain bioactive compounds such as essential oils (EO), valuable in several industries (2). This study focused on EO extraction from Oro miel and Crespa pineapple peels using microwave-assisted hydrodistillation (MAHD) with Natural Deep Eutectic Solvents (NADES). Various NADES were formulated and characterized. Extraction conditions were optimized, and the best ones were applied to MAHD using NADES. Finally, EO were analyzed by GC-MS, revealing differences in volatile profiles between the two pineapple varieties.
Keywords: Hydrodistillation, NADES, pineapple varieties, GC-MS and residues